Penerapan SD-Preneur di SD Muhammadiyah Cipete, Cilongok, Banyumas Pasca Pandemi Covid-19 - Melia Hardiana; W Wakhudin (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2022)
This research aimed to describe the implementation of SD Preneur at SD Muhammadiyah Cipete Cilongok after the Covid-19 pandemic. This research method uses qualitative research methods with descriptive design. Collecting data in this study using interview, observation, and documentation techniques. The data analysis procedure goes through data reduction, data display, conclusion drawing and verification. The validity of the data is using triangulation of sources and triangulation of techniques. The results show that to improve the welfare of school residents, SD Muhammadiyah Cipete is not enough to organize entrepreneurship conventionally but also implement entrepreneurship with the SD-Preneur model. The SD-Preneur model entrepreneur is the principal as person in charge. The implementer, namely the principal and SD Preneur at SD Muhammadiyah Cipete, Cilongok, has taken the form of BUMS or School-Owned Enterprises.